1995
DOI: 10.1007/bf01451575
|View full text |Cite
|
Sign up to set email alerts
|

Lectin binding defines and differentiates M-cells in mouse small intestine and caecum

Abstract: M-cell surface glycoconjugate expression was investigated by applying a panel of lectins to whole fixed mouse Peyer's and caecal patches. While the majority of lectins failed to identify mouse M-cells, the lectin Euonymus europaeus differentially stained the surface of M-cells in both mouse Peyer's and caecal patches, and the lectins Ulex europaeus II and Bandeiraea simplicifolia I isolectin B4 identified M-cells in the Peyer's and caecal patch follicle associated epithelium, respectively. These three mouse M-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Although some of the confocal images gave the impression that three subtypes of M-cells could exist according to the expression of ␣ 1-2-linked fucose or GalNAc, at the electron microscopic level no distinct subtypes were found, but rather a continuous spectrum of labeling intensities. Heterogeneity among the M-cells of individual domes has likewise been reported for the binding of the lectins UEA-I, AAA, and EEA to M-cells of murine Peyer's and cecal patches (Giannasca et al 1994;Clark et al 1995) and for the binding of UEA-I and Lotus lectin to M-cells in the palatine tonsil of rabbits (Gebert 1996). The lectin labeling of living tissue performed in the present study demonstrates that variations in the saccharide composition of the apical membrane of M-cells indeed exist in the living system, which probably play a role in the differential adherence to and uptake of antigens by M-cells.…”
Section: Discussionmentioning
confidence: 75%
“…Although some of the confocal images gave the impression that three subtypes of M-cells could exist according to the expression of ␣ 1-2-linked fucose or GalNAc, at the electron microscopic level no distinct subtypes were found, but rather a continuous spectrum of labeling intensities. Heterogeneity among the M-cells of individual domes has likewise been reported for the binding of the lectins UEA-I, AAA, and EEA to M-cells of murine Peyer's and cecal patches (Giannasca et al 1994;Clark et al 1995) and for the binding of UEA-I and Lotus lectin to M-cells in the palatine tonsil of rabbits (Gebert 1996). The lectin labeling of living tissue performed in the present study demonstrates that variations in the saccharide composition of the apical membrane of M-cells indeed exist in the living system, which probably play a role in the differential adherence to and uptake of antigens by M-cells.…”
Section: Discussionmentioning
confidence: 75%
“…Consistent with this idea is the expression of different glycoconjugates by distinct functional classes of cells in the visual (Chan et al, 1999), respiratory (Kasper and Singh, 1995;BurkhardtHolm, 1997;Dorscheid et al, 1999), gustatory (Zeng et al, 1995), olfactory (Taniguchi et al, 1993;Shnayder-Shapiro et al, 1995;Nakajima et al, 1998;, gastrointestinal (Sato and Spicer, 1982;Falk et al, 1994;Ge et al, 1998;Gebhard and Gebert, 1999;Poorkhalkali et al, 1999), reproductive (Zhou et al, 1994;Arenas et al, 1998;Romo et al, 1999), and immune (Clark et al, 1995;Sharma et al, 1996;Foster et al, 1998) systems in a variety of mammalian species.…”
Section: Discussionmentioning
confidence: 94%
“…A similar analysis, performed approximately 6 months after Cre induction, showed that the FAE retained LacZ ϩ cells. To detect M cells within these ribbons of blue cells, sections were stained with the lectin Ulex europaeus agglutinin 1 (UEA-1), a specific M cell marker (9), (5). Although the lectin also detects glycoproteins on Paneth and goblet cell membranes, these cell types are never seen in the FAE when sections are stained for lysozyme or periodic acid Schiff's, respectively.…”
Section: Cells Derive From Lgr5 Stem Cellsmentioning
confidence: 99%